Structural performance of corroded reinforced concrete beams made with fiber-reinforced self-compacting concrete. (August 2021) - Rajesh Kumar, K.; Shyamala, G.; Adesina, A.
Abstract: The structural performance of corroded beams made with fiber-reinforced self-compacting concrete (SCC) was evaluated in this study. SCC samples reinforced with glass chopped fibers (GF) and polypropylene fibers (PF) without steel reinforcement were first made and assessed in terms of fresh properties, compressive strength, and flexural strength. Cylindrical SCC samples were then subjected to accelerated corrosion in order to determine the influence of SCC mixtures on the steel reinforcement corrosion in terms of the mass loss. Deep beams with a dimension of 700 mm × 100 mm × 300 mm were then made with selected mixtures and subjected to accelerated corrosion before evaluating the structural performance. Findings from this study showed that fiber-reinforced SCC can be utilized in the production of reinforced concrete without any detrimental effects on fresh and mechanical properties. The incorporation of GF and PF at a dosage of 0.06% and 0.1%, respectively enhanced the 90 days compressive strength and flexural strength by 15.4% and 40.8% compared to reinforced concrete made with plain SCC. Results from this study also showed that the use of fiber-reinforced SCC enhanced the structural performance of corroded beams in terms of flexural load capacity, stiffness, ductility and ultimate energy.